2015
DOI: 10.1590/0102-311x00036114
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying and adolescent mental health: systematic review

Abstract: Cyberbullying is a new form of violence that is expressed through electronic media and has given rise to concern for parents, educators and researchers. In this paper, an association between cyberbullying and adolescent mental health will be assessed through a systematic review of two databases: PubMed and Virtual Health Library (BVS). The prevalence of cyberbullying ranged from 6.5% to 35.4%. Previous or current experiences of traditional bullying were associated with victims and perpetrators of cyberbullying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
171
0
43

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(226 citation statements)
references
References 34 publications
12
171
0
43
Order By: Relevance
“…Both physical violence and cyber-victimization were strongly associated with current PTSD in our sample. Recent school-based studies have reported U.S. cyberbullying rates of 15–16% 33,86,87 (ranging from 6–35% internationally) 88 , and physical peer violence rates of approximately 25% 87 , using similar measures. The high prevalence of both physical and cyber-violence in our ED population is concerning, particularly since they were so strongly associated with PTSD in this sample.…”
Section: Discussionmentioning
confidence: 97%
“…Both physical violence and cyber-victimization were strongly associated with current PTSD in our sample. Recent school-based studies have reported U.S. cyberbullying rates of 15–16% 33,86,87 (ranging from 6–35% internationally) 88 , and physical peer violence rates of approximately 25% 87 , using similar measures. The high prevalence of both physical and cyber-violence in our ED population is concerning, particularly since they were so strongly associated with PTSD in this sample.…”
Section: Discussionmentioning
confidence: 97%
“…Although the study implied that some social harm were emerged from social networking, but it could be supposed that the social behaviors hidden by traditional barriers are found out through social networks; hence, there is an ambiguity about the causal direction of the association between bullying and social networking (15).…”
Section: Discussionmentioning
confidence: 99%
“…Bullying prevalence is widely studied in many countries and is ranging from 8.6% to 45.2% in males, and from 4.8% to 35.8% in females (14) and cyber bullying ranged from 6.5% to 35.4% (15). Two studies in Iran indicated that the prevalence of bullying were 64.2% and 26.3% (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Cyber victims and cyberbullies face more emotional and psychosomatic problems, which further leads to social difficulties and feeling of being unsafe. Cyberbullying is often associated with severe depressive symptoms, ideation and substance use and even suicide attempts (17). These problems lead to poor psychosocial health and reduce productivity of the individual.…”
Section: Social Media As Threatmentioning
confidence: 99%